Initial Experimental Results of Real-Time Variant Pose Face Detection and Tracking System - Nur Baiti, Zahir; Rosdiyana, Samad; Mahfuzah, Mustafa (2013)
A face detection system is a computer application for automatically detecting a human face from digital image or video frame. This paper presents a face detection system that used web camera to detect and track a face in real-time. To detect a face in the image, a simple method of skin color detection is used. By using color detection method in this project, the face can be segmented easily from the complex background. However, to detect a face in real-time is quite challenging especially when a face is moving and the real-time environment has uneven illumination. This paper presents the preliminary result of face detection and tracking system, which is the system, detects a face that has different poses in a real-time situation, where the light condition is uneven. Here, to complete the detection process, contour detection method is added so that the detection is more accurate. This system can be applied in many applications such as banking system to reduce the number of forgery, security system, and human-computer interaction (HCI).